The making of land use decisions, war, and state. Issue 4 (4th July 2021) - Lundsgaard-Hansen, Lara M.; Metz, Florence; Fischer, Manuel; Schneider, Flurina; Myint, Win; Messerli, Peter
ABSTRACT: During a civil war and its aftermath, rival powerholders frequently engage in decision-making over land use, for example, via land acquisitions or legal reforms. This paper explores how powerholders influence land use decision-making and what their engagement implies for territorial control. We analyse three cases of land use changes in Myanmar's south between 1990 and 2015, where the Myanmar state and an ethnic minority organization fought over territorial control. We gathered qualitative data with a mix of methods and visualised actor networks and institutions. Our analysis reveals that the state managed to increasingly control decision-making over local land use from a distance by employing actor alliances and institutions such as laws and incentives, whereas the ethnic organization lost influence. We conclude that engaging in land use decision-making plays a crucial role in influencing the outcomes of a civil war and that it represents a form of war- and state-making.